Protective Effect of Patchouli Alcohol Against High-Fat Diet Induced Hepatic Steatosis by Alleviating Endoplasmic Reticulum Stress and Regulating VLDL Metabolism in Rats - Xue Wu; Nan Xu; Minyao Li; Qionghui Huang; Jiazhen Wu; Jiazhen Wu; Yuxuan Gan; Liping Chen; Huijuan Luo; Yucui Li; Xiaoqi Huang; Ziren Su; et al. (Frontiers Media S.A., 2019)
Nonalcoholic fatty liver disease (NAFLD) is currently the most common chronic hepatic disorder worldwide. The earliest stage of NAFLD is simple steatosis, which is characterized by the accumulation of triglycerides in hepatocytes. Inhibition of steatosis is a potential treatment for NAFLD. Patchouli alcohol (PA) is an active component of Pogostemon cablin (Blanco) Benth. (Labiatae), which is a medicinal food in Asia countries and proved to possess hepatoprotective effect. This research aimed to investigate the effectiveness of PA against high fat diet (HFD)-induced hepatic steatosis in rats. In this study, male Sprague Dawley rats were fed a HFD for 4 weeks to induce NAFLD. Oral administration with PA significantly reduced pathological severity of steatosis in HFD-fed rats. It was associated with suppressing endoplasmic reticulum (ER) stress and regulating very low-density lipoprotein (VLDL) metabolism. Our data showed that PA treatment effectively attenuated ER stress by inhibiting the activation of protein kinase-like ER kinase (PERK), inositol-requiring transmembrane kinase/endoribonuclease 1 (IRE1), and activating transcription factor 6 (ATF6). Moreover, PA decreased hepatic VLDL uptake by suppressing very low-density lipoprotein receptor (VLDLR) expression. It also restored VLDL synthesis and export by increasing apolipoprotein B100 (apoB 100) secretion and microsomal triglyceride-transfer protein (MTP) activity. Taken together, PA exerted a protective effect on the treatment of NAFLD in HFD-fed rats and may be potential therapeutic agent acting on hepatic steatosis.